Comprehensive Cervical Cancer Prevention in Tanzania (CONCEPT) study: Cohort profile - Ditte Søndergaard Linde; Vibeke Rasch; Julius D Mwaiselage; Rachel Manongi; Patricia Swai; Chunsen Wu; Bariki Mchome; Johnson Katanga; Crispin Kahesa; Susanne Kjaer (BMJ Open)
Purpose Cervical cancer is a major cause of death among women in Eastern Africa, and the distribution of human papillomavirus (HPV) according to HIV status is inadequately characterised in this region. In order to guide future cervical cancer preventive strategies that involve HPV testing, the Comprehensive Cervical Cancer Prevention in Tanzania (CONCEPT) study was established in 2015. The CONCEPT cohort aims to investigate the natural history of HPV and determine acquisition and persistence patterns of high-risk (HR) HPV among HIV-positive and HIV-negative women. Further, the influence of lifestyle and sexual/reproductive factors will be investigated. The main objective of this article is to describe how the CONCEPT cohort was established.Participants Women aged 25–60 years were enrolled from cervical cancer screening clinics in Dar-es-Salaam and Moshi, Tanzania. Data were collected at baseline, at 14 months (first follow-up) and at 28 months (second follow-up). Biological samples included two cervical swabs for careHPV DNA testing, cytology, Hybrid Capture 2, genotyping and blood samples for HIV. Visual inspection with acetic acid was performed, and sociodemographic, lifestyle and sexual/reproductive characteristics were collected through a standardised questionnaire.Findings to date 4043 women were included in the cohort from August 2015 to May 2017. At baseline, 696 (17.1%) women were HR HPV positive, and among these, 31.6% were HIV positive; 139 women (3.4%) had high-grade squamous intraepithelial lesions. 3074 women (81%) attended the first follow-up. The majority attended after receiving a phone call reminder (35%) or from home via self-samples (41%). At first follow-up, 438 (14.4%) were HR HPV positive and 30.4% of these were HIV positive.Future plans A second follow-up is underway (17 December 2018–October 2020). We plan to integrate our data with a previous cross-sectional HPV study from Tanzania to increase the power of our findings. Researchers interested in collaborating are welcomed, either by extracting data or jointly requesting further investigation from the cohort.